Characterization of the craniofacial abnormalities of the homozygous G608G progeria mouse model - Beeram, Indeevar; Cubria, Maria Belen; Kamalapathy, Pramod; Yeritsyan, Diana; Dubose, Amanda J.; Razavi, Ahmad Hedayatzadeh; Nafisi, Nazanin; Erdos, Michael R.; Snyder, Brian D.; Cabral, Wayne A.; Collins, Francis S.; Nazarian, Ara (Frontiers in Physiology, 2024)
IntroductionHutchinson-Gilford Progeria Syndrome (HGPS) is a rare genetic condition characterized by premature aging, impacting multiple organ systems, including cardiovascular, musculoskeletal, and integumentary. Significant abnormalities in a transgenic mouse model (homozygous G608G mutation), specifically targeting the development of skull and facial bone indices through high-resolution CT scanning and cephalometric analysis.MethodsKey measurements include bone thickness, skull volume, and cranial suture integrity. Bone volume increased significantly in HGPS mice by 8 months of age compared to wildtype mice.ResultsCortical thickness showed a trend toward increased values in HGPS mice. Cranial metrics revealed distinct differences.DiscussionHGPS mice exhibited smaller internasal width, interzygomatic distance, and palatine length compared to WT mice over time.